Arthur, clean your room! - Brown, Marc Tolon (New York : Random House, 1999)
His sister D.W. convinces Arthur to have a garage sale after his mother tells him to get rid of the junk in his room, but things do not work out exactly as he had planned.
Keywords: Aardvark -- Fiction; Orderliness -- Fiction; Garage sales -- Fiction; Brothers and sisters -- Fiction